Pengaruh Stress Kerja dan Budaya Organisasi Terhadap Kinerja Karyawan Pada PT. Perisai Bintang Sakti - Sabita An Nafisah; Fauziah Afriyani; Try Wulandari (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
The purpose of this study is to analyze the effect of work stress and organizational culture on employee performance at PT Perisai Bintang Sakti. The theory used in this study is related to work stress, organizational culture and employee performance. This study used a type of quantitative research with data collection using a questionnaire. The total population in this study is 50 employees with a saturated sample technique. Data analysis techniques in this study used data quality tests, classic assumption tests, multiple linear regression analysis, t tests, F tests and the coefficient of determination. From the results of tests conducted partially work stress has a negative and significant effect on employee performance, organizational culture has a positive and significant effect, and simultaneously work stress and organizational culture have a significant effect on employee performance. This research suggests that companies always organize and pay attention to the level of employee work stress by holding joint entertainment such as joint karaoke can reduce work stress due to the workload provided, it is necessary to establish good cooperation with employees and division heads with the aim that more monitoring of employee activities can run well.